Il governo dell’informale come problema di egemonia - De Nicola, Alberto (Cambio. Rivista sulle Trasformazioni Sociali, 2021)
This paper intends to propose a critical examination of some of the theoretical orientations that have most characterized the debate on the informal economy in recent years. The reflection will take welfare regimes as a research field for analyzing the impact of informality on institutional systems. The paper will be divided into two parts. In the first one, structuralist, geographical and governmental approaches to informality will be discussed, showing some theoretical limits in their interpretation of the plurality of social practices and institutional change. In the second part, some indications will be proposed on how to understand the role of informality on institutional systems starting with a review of some Gramscian notions relating to the problems of normativity and historical change.